HUMAN EXPLOITATION AS SOCIAL INEQUALITY REFLECTED IN THE NOVEL OLIVER TWIST BY CHARLES DICKENS - Adisty Indah Prahastini; Siti Hafsah; Sumardjo Sumardjo (Faculty of Letters Universitas Balikpapan, 2019)
The aim of this research is to explore the kinds of human exploitation and social inequality in the novel “Oliver Twist”. The objectives of this research are to find and to describe the forms of human exploitation in the novel Oliver Twist by Charles Dickens, and to find the connection between social inequality and human exploitation in the novel Oliver Twist by Charles Dickens. The theory used in this research is exploitation and social inequality based in Marxism theory by Karl Marx. The methodology is qualitative research in which the researcher used to present the issues descriptively. The data were collected from the narration and dialogue in the novel, the data were analyzed descriptively using the theory.After going through the analysis, the researcher concludes that the forms of human exploitation in the novel Oliver Twist by Charles Dickens are child exploitation which consist of doing anything as compulsory, fact manipulated, unequal treatment, unequal facility, cruel punishment also child trafficking, and the other one are women exploitation which consist of become a servant and prostitute. Whereas the connection between social inequality and exploitation is triggered by the class differences between the upper class dan the lower class.